DEVELOPING INTERACTIVE PPT AS LEARNING MEDIA FOR WRITING SKILL IN ELEVENTH GRADE MIA CLASS AT MA BUSTANUL MUTAALIMIN - Kanti Rahayu; Tyas Alhim Mubarok; Ahmad Saifudin (IKIP Siliwangi, 2023)
Computer-based media has been widely known and used as learning media in the classroom, it has proven effective in supporting teachers in conveying learning. One of them is PowerPoint media which is created according to the creativity and needs of the teacher. However, the lack of motivation in the classroom can make students less interested in understanding learning objectives. This can be seen from the lack of enthusiasm of students in learning English so that they are weak in these subjects, especially in writing skills. This project aims to develop an Interactive PPT to facilitate students' continuous learning and train students' activeness, especially in writing skills in class, so that learning English can take place optimally. This study uses the Research and Development (R&D) method with the ADDIE model which is a development of the Dick and Carrey model. In collecting data in research, researchers used questionnaires when observing students, structured interviews with subject teachers, validation questionnaires, and also student response questionnaires. Keywords: English Language Teaching; Interactive PPT; Learning Media; Writing Skill